Konsep ergonomi kultural Nusantara dalam pendidikan dasar Desain Produk ITENAS - Edi Setiadi Putra; Mohamad Arif Waskito (Institut Seni Indonesia Yogyakarta, 2020)
This study aims to reveal the existence of the concept of Cultural Ergonomics or Ergoculture, as a relevant term to describe the cultural influence of a nation in the principles of modern ergonomics. Ergonomics or Human Factor, is one of the important sciences to be studied by Product Design students, because it is a determining factor in achieving the predicate of the feasibility of using a product. Comfortability factors, efficiency and productivity are the benchmarks for the success of product design process. The study in this paper is a review of the process of design basic education that needs to introduce the ergonomic aspects of Indonesian people to a particular field of work based on cultural values. Not all principles of universal ergonomics are relevant to the cultural patterns of Indonesian society. Ergonomics studies in essential design basic education are delivered early to strengthen the understanding of cultural values from the ergonomic point of view of Indonesian society in general. This study is the beginning of the thought of the need to strengthen cultural aspects in Ergonomics applied to the study of Industrial Product Design in Indonesia.